BOOK REVIEW OF DANIELLE STEEL’S KALEIDOSCOPE - Dethan, Norman (LANTERN (Journal on English Language, Culture and Literature), 2016)
Novel is a long narrative, normally in prose, which describes fictional characters and events, usually in the form of sequential story. Kaleidoscope is a novel for adults that talks about the journey of life. This novel is written by a famous novelist Danielle Steel. In this novel we can see a lot of tragedy and drama, the characters are a little bit over the top but the overall story of this novel always makes us curious about the ending of the story.